Penerapan Media Roda Putar (Spinning Wheel) Dalam Meningkatkan Kosakata Bahasa Arab di MTs N 10 Jember - Syaharani, Indry; Bukhori, Evi Muzaiyidah; Aimmah, Muftiatul (Rausyan Fikri Journal of Islamic Studies, 2023)
The rotating wheel is a circle that can be rotated and divided into several sectors/parts inwhichtherearequestioncards.Oneinterestingwaytoimprovemasteryofmufrodatandto make it easier for students to remember mufrodat is to use a rotating wheel, which isexpectedtobeabletoimprovestudents'abilities,especiallyinincreasingstudents'vocabulary. The main aim of learning Arabic mufradat is to introduce new vocabulary tostudents either through, train students to be able to pronounce the vocabulary properly andcorrectly, understand the meaning of vocabulary, both denotatively or lexically and whenused in the context of certain sentences. Mastery of mufradat is a person's understandingand ability to use or master mufradat in communication. The method used in this researchis a descriptive qualitative research method. Data collection techniques use expert theoriestaken from some books and scientific journals. Actions used in this research is rotatingwheelmedia.Roda putar berbentuk lingkaran yang dapat diputar dan dibagi menjadi beberapasektor/bagian yang didalamnya terdapat kartu soal. Salah satu cara yang menarik untukmeningkatkanpenguasaanmufrodatdanuntukmemudahkansiswadalammengingatmufrodat adalah dengan menggunakan media roda putar, yang diharapkan mampu untukmeningkatkankemampuansiswakhususnyadalammeningkatkankosakatasiswa.Tujuanutama pembelajaran mufradat bahasa Arab adalah memperkenalkan kosakata baru kepadasiswa baik, memahami makna kosakata, baik secara denotatif maupun leksikal dan biladigunakan dalam konteks kalimat tertentu. Penguasaan mufradat adalah pemahaman dankemampuanseseorangdalammenggunakanataumenguasaimufradatdalamberkomunikasi. Teknik yang digunakan dalam penelitian ini adalah strategi eksplorasiilustratif subjektif. Strategi pengumpulan informasi memanfaatkan spekulasi utama yangdiambil dari beberapa buku dan catatan harian logis. Kegiatan yang digunakan dalameksplorasiiniadalahmedia roda berputar.